Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Bank Syariah - Tasini Tasini; Suciati Muanifah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. The main objective of Financial Performance is to evaluate how effectively an entity manages its finances. Overall, Sharia financial performance does not only prioritize financial profit aspects alone, but also considers the social, environmental and ethical impacts of financial activities in accordance with Islamic Sharia principles. The comprehensive final assignment aims to critically review the factors that influence the Financial Performance of Sharia banks. The results of the discussion conclude: Based on the description of the three journals analyzed in this critical review, the author concludes that the factors that influence financial performance are (1) Financing for buying and selling, one of the products that is in demand by Sharia banking. Its easy-to-use mechanism for short-term investments is one of the reasons why this product is in demand. So the more the financing for buying and selling distributed by Sharia Commercial Banks (BUS), the better the financial performance. (2) Profit-sharing financing, financing that uses a cooperation agreement between the bank and the customer where profits and losses are agreed upon at the beginning of the agreement. With the increasing amount of funds invested by Sharia Commercial Banks (BUS), the level of profitability of Sharia Commercial Banks (BUS) is also high. (3) Non-Performing Financing, is the ratio of failures in credit distribution. Therefore, the higher the Non-Performing Financing (NPF) value, the worse it will be for banking. Conversely, the lower the Non-Performing Financing (NPF) value, the better it will be for financial performance.